The Role of Supply Chain: Capability and Flexibility to Improve Performance: (Study at PT. Sumber Djaja) (Fakultas Bisnis, 2022)
The increase in the development of the expedition business from year to year requires companies to maintain competitive advantage in order to maintain product quality, relationship with partners, and improve company’s performance. The object of this study is a trucking company named PT. Sumber Djaja, which was founded in 1970, where they saw a decline in performance as time goes by. This study aims to see the effect of supply chain capabilities and supply chain flexibility on the business performance of PT. Sumber Djaja. The method used in this research is quantitative, with a research sample of 45 respondents using purposive sampling method. Data collection was carried out using questionnaire and analyzed using Partial Least Squares method. The results of data analysis showed that supply chain capability and supply chain flexibility have a significant effect on business performance.